Nedaplatin and paclitaxel compared with carboplatin and paclitaxel for patients with platinum-sensitive recurrent ovarian cancer - Ge, Li (Am J Cancer Res, 2018)
This retrospective cohort study was designed to evaluate the efficacy and safety of nedaplatin plus paclitaxel (NP) compared with carboplatin plus paclitaxel (CP) in platinum-sensitive recurrent ovarian cancer. Patients with histologically proven epithelial ovarian cancer with recurrent interval ≥6 months after finishing platinum-based therapies between January 1, 2009 and December 31, 2014 were investigated. Patients received an intravenous infusion of NP (nedaplatin 80 mg/m(2) plus paclitaxel 175 mg/m(2)) or CP (carboplatin at an area under the curve of 5 plus paclitaxel 175 mg/m(2)) protocols every 3 weeks for at least 6-8 cycles or until disease progression. Primary end point was progression-free survival (PFS); secondary end points were toxicity and overall survival (OS). 436 patients were included in the study, containing 241 cases receiving CP regimen and 195 cases receiving NP regimen, who were all contained in safety analysis. Because of 61 patients with unbearable toxicity and poor compliance, 375 patients were finally included in the efficacy analysis. With median follow-up of 63.5 months, PFS was 11.0 months with NP regimen versus 9.5 months with CP regimen (P=0.109). Subgroup analysis indicated that PFS of the NP arm was statistically superior to the CP arm when recurrent interval was 6-12 months (P=0.048); median PFS was 10.0 versus 8.0 months, respectively. There was no significant difference in overall survival between two groups. More frequent grade 3-4 neutropenia (13.3% vs 33.6%), thrombocytopenia (5.6% vs 14.5%) and hypersensitivity reactions (5.6% vs 21.9% ) were observed in CP arm (P<0.01). Compared to the CP, NP regimen did not improve 5-year overall survival in platinum-sensitive recurrent ovarian cancer, but it had better tolerance. NP obtained significant benefit in progression-free survival when the recurrent interval was between 6 and 12 months, although the efficacy of two regimens were similar when the recurrent interval ≥12 months.